2016
DOI: 10.1089/aid.2015.0300
|View full text |Cite
|
Sign up to set email alerts
|

Increases in NKG2C Expression on T Cells and Higher Levels of Circulating CD8+B Cells Are Associated with Sterilizing Immunity Provided by a Live Attenuated SIV Vaccine

Abstract: Vaccines based on live attenuated viruses are highly effective immunogens in the simian immunodeficiency virus (SIV)/rhesus macaque animal model and offer the possibility of studying correlates of protection against infection with virulent virus. We utilized a tether system for studying, in naive macaques and animals vaccinated with a live-attenuated vaccine, the acute events after challenge with pathogenic SIV. This approach allowed for the frequent sampling of small blood volumes without sedation or restrain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 54 publications
(60 reference statements)
0
2
0
Order By: Relevance
“…These findings might suggest that the observed increase in NKG2C-expressing NK cells upon pandemic influenza vaccination is due to adjuvantation with AS03. However, the immunization of macaques with a live attenuated SIV vaccine and a subsequent challenge was found to result in elevated frequencies of NKG2C-expressing circulating T cells in vaccinated but not unvaccinated animals [ 38 ]. Another study with SIV-infected rhesus macaques demonstrated the NK cell-mediated killing of antigen-pulsed DCs in a NKG2C-dependent manner [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…These findings might suggest that the observed increase in NKG2C-expressing NK cells upon pandemic influenza vaccination is due to adjuvantation with AS03. However, the immunization of macaques with a live attenuated SIV vaccine and a subsequent challenge was found to result in elevated frequencies of NKG2C-expressing circulating T cells in vaccinated but not unvaccinated animals [ 38 ]. Another study with SIV-infected rhesus macaques demonstrated the NK cell-mediated killing of antigen-pulsed DCs in a NKG2C-dependent manner [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, many LAV strategies have been evaluated in NHPs using live-attenuated simian immunodeficiency virus (SIV) [204][205][206][207][208][209], the simian version of HIV-1 that only replicates in NHP species. Additional strategies employing HIV-1 related viruses [210,211] or engineered viruses harboring HIV-1 or SIV antigens [212,213] have also been tested in NHPs. NHPs have also been employed to investigate and/or evaluate the immunogenicity of many other LAVs, such as viral vectors harboring Ebola virus glycoproteins [214][215][216][217][218], LAIV [195], OPV [189,190], MV-LAV [150,185,197,[219][220][221], BCG [156], live-attenuated Venezuelan equine encephalitis virus [222], YFV-17D [151] or live-attenuated Zika virus [43].…”
Section: Of Mice Men and Non-human Primatesmentioning
confidence: 99%